The violation of human rights in jail:proposals to claim the human dignity of the penitentiary internal citizen and promote the exercise of its rights - Ríos Patio, Gino (2017)
The prison as a penalty is intended only for the suspension of the exercise of the right to personal ambulatory freedom, however, in practice, it has denied certain civil, political, economic, social and cultural rights. Maintains until now, with serious detriment to the axiological foundation of the democratic state and law, without anyone doing anything about it. This criminal institution is not only marked by overcrowding and tugurization, derived from a denigrating penitentiary system and an illegitimate criminal system, but reproduces social discrimination within a highly corrupt environment. It proposes some concrete alternatives  of  criminological policy for the state to fulfill its obligation to respect, promote and defend the human rights of internal persons in penal establishments.